The effect of pre-mutation of X chromosome CGG trinucleotide repeats on brain anatomy. - Moore, C; Daly, E; Tassone, F; Tysoe, C; Schmitz, N; Ng, V; Chitnis, X; McGuire, P; Suckling, J; Davies, K; Hagerman, R; Hagerman, P; et al. (2004)
Expanded trinucleotide repeats are associated with several neuropsychiatric disorders, including fragile X syndrome (FraX) which is the most common inherited form of mental retardation. It is currently thought that FraX results from having >200 CGG trinucleotide repeats, with consequent methylation of the fragile X mental retardation gene (FMR1) and loss of FMR1 protein (FMRP). Pre-mutation carriers of FraX (with 55-200 CGG trinucleotide repeats) were originally considered unaffected, although recent studies challenge this view. However, there are few studies on the effect of pre-mutation trinucleotide repeat expansion on the male human brain using quantitative MRI. Also the results of prior investigations may be confounded because people were selected on the basis of clinical and neurological features, and not genetic phenotype. We compared the brain anatomy of 20 adult male pre-mutation members of known FraX families with 20 healthy male controls. The two groups did not differ significantly in age, intelligence quotient (IQ) or handedness. We also investigated whether any observed effects were associated with: (i) ageing; (ii) expansion of pre-mutation CGG trinucleotide repeats; (iii) reduction in the percentage of lymphocytes staining with anti-FMRP antibodies [%FMRP(+) lymphocytes]; and (iv) elevation of FMR1 mRNA levels. Male pre-mutation carriers of FraX, compared with matched controls, had significantly less voxel density in several brain regions, including the cerebellum, amygdalo-hippocampal complex and thalamus. Within pre-mutation carriers of FraX, ageing, increases in the number of CGG trinucleotide repeats and decreases in %FMRP(+) lymphocytes were associated with decreasing voxel density of regions previously identified as decreased relative to controls. Regional grey and white matter density is significantly affected in male pre-mutation carriers of FraX recruited on the basis of genetic, not clinical, phenotype. The association of voxel density reduction and ageing is consistent with observations of a subgroup of older pre-mutation males who present with cognitive decline. Moreover, our findings suggest, for the first time, an association between voxel density reduction and genetic variation in FraX.